Controlling factors of rainwater and water vapor isotopes at Bangalore, India: Constraints from observations in 2013 Indian monsoon. Issue 23 (13th December 2016) - Rahul, P.; Ghosh, Prosenjit; Bhattacharya, S. K.; Yoshimura, Kei
Abstract: Isotopic ratios of rainwaters are believed to decrease with the amount of rainfall. However, analyses of the isotopic composition of rainwater and water vapor samples collected from Bangalore during the monsoon period of 2013 fail to show any simple relationship with the local meteorological parameters whereas show good correlation with the regional integrated convective activity. The correlation is particularly high when the averaging is done over the preceding 8 to 15 days, showing the influence of mixing or residence time scale of atmospheric moisture. This observation emphasizes the role of regional atmospheric circulation driving the isotopic values. A comparison between observed isotope ratios in water vapor and rainwater with Isotope‐enabled Global Spectral Model shows discrepancies between the two. The observed values are relatively enriched, indicating a systematic bias in the model values. The higher observed values suggest underestimation of the evaporation in the model, which we estimate to be about 28 ± 15% on average. Simultaneous analyses of rainwater and water vapor isotopic composition again show definitive presence of raindrop evaporation (31 ± 14%). We also documented a distinct pattern of isotopic variation in six samples collected at Bangalore due to mixing of vapor from a cyclonic system in close proximity that originated from the Bay of Bengal. It seems that large‐scale isotopic depletion occurs during cyclones caused by Rayleigh fractionation due to massive rainout. These results demonstrate the power of rainwater and water vapor isotope monitoring to elucidate the genesis and dynamics of water recycling within synoptic‐scale monsoon systems. Key Points: Using observations on isotopic composition of rain and water vapor at Bangalore, the amount effect is evaluated from the convective activity The raindrop evaporation is suggested from simultaneous isotopic analysis of rainwater and water vapor and using a global isotopic model Anomalous isotopic depletions with a depression system show contribution of proximal vapor that has undergone intense Rayleigh effect